Effect of dynamic and static strength training on hormonal activity in elite boxers - Aggön, E.; Agirbas, Ö.; Alp, H. H.; Uçan, I.; Gürsoy, R.; Hackney, A. C. (Baltic Journal of Health and Physical Activity, 2020)
Background: The aim of this study was to determine hormonal responses to acute and chronic exposure to static and dynamic strength training programs using resistance bands in boxers. Material and methods: 19 male national boxers participated in the study. Boxers were instructed to perform strength exercises with resistance bands for 3 days a week for 8 weeks involving either dynamic (n=10) or static (n=9) resistance exercises. Blood samples were taken before exercise, immediately after the initial exercise session, and 8 weeks later following the last exercise session. Cortisol, growth hormone, adrenocorticotropic hormone adrenaline and noradrenaline levels were measured. Statistical analyses involved non-parametric analysis with an alpha level of .05. Results: Dynamic strength exercises were effective stimuli to growth hormone, adrenaline and noradrenaline, while static strength exercises provoked cortisol, growth hormone, adrenaline and noradrenaline responses both initially after exercise and after 8 weeks of chronic training. Neither dynamic nor static strength exercises were effective in prompting adrenocorticotropic changes after an exercise session or after 8 weeks of training. Conclusions: We showed that dynamic and static strength exercise protocols using resistance bands both could provoke acute and chronic hormonal responses in boxers similar to more traditional modes of such exercise.